Light Intensity Modulates the Effect of Phosphate Limitation on Carbohydrates, Amino Acids, and Catechins in Tea Plants (Camellia sinensis L.) - KC, Santosh; Long, Lizhi; Liu, Meiya; Zhang, Qunfeng; Ruan, Jianyun (Frontiers in Plant Science, 2021)
Metabolites are major contributors to the quality of tea that are regulated by various abiotic stresses. Light intensity and phosphorus (P) supply affect the metabolism of tea plants. However, how these two factors interact and mediate the metabolite levels in tea plants is not fully understood. The present work was to investigate the consequences on metabolism of carbohydrates, amino acids and flavonoids of different light and P regimes in the Fengqing tea cultivar. The leaves and young shoots were subjected to untargeted metabolomics analysis by GC×GC–TOF/MS, UPLC–Q–TOF/MS and targeted analysis by HPLC along with quantification of gene expression by qRT–PCR. The results from young shoots showed that amino acids, pentose phosphate and flavonol glycosides pathways were enhanced in response to decreasing light intensities and P deficiency. The expression of the genes HK1, RPIA, GS1, P4H and arg was induced by P limitation, thereafter affecting carbohydrates and amino acids metabolism where shading modulated the responses of transcripts and corresponding metabolites caused by P deficiency. P deprivation repressed the expression of SPX2 and induced SWEET3 and AAP which ultimately caused an increase in the amino acids; Glu, Pro and Arg under shading but decreased catechins (ECG and GA) content in young shoots.